Assessment of Nutritional Status of Grade 1-11 Schoolchildren in Lviv - S.L. Niankovskyi; I.P. Pasichniuk (Zaslavsky O.Yu., 2016)
The article presents the results of studies on the features of nutritional status of 90 grade 1-11 pupils from comprehensive secondary schools in Lviv. It was found that in the majority of them, daily dietary intake was substantially unbalanced, with excess of energy and proteins on the background of a lack of microelements and vitamins. Elementary school pupils with insufficient body weight (10 %) had energy supply deficit due to reduced consumption of fats, lack of micronutrients, vitamins. In contrast, among pupils of grades 5-8 and 9-11, 20 % of children had overweight associated with an imbalanced intake of important nutrients on the background of increased consumption of high-calorie foods. These investigations demonstrate the need of nutritional correction and lifestyle modification in pupils to prevent metabolic disorders and their effects, improving health status.